Determinants of R&D Value Reporting Bias: An Empirical Study in the EU (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This study investigates the determinants of R&D value reporting bias in technology sector entities from six EU countries, including Germany and France, using data from 188 entities between 2006 and 2023. The research employs a mixed-method approach, including Pearson correlations, mixed model regressions, and binary logistic regressions, to analyse the relationships between financial leverage ratios, earnings per share, and the performance of intangible assets. The findings indicate significant correlations between financial structure metrics and the Net Present Value (NPV) ratios of intangible assets, suggesting that higher debt levels relative to assets enhance the performance of internally generated intangibles, while increased debt-to-equity and debt-to-capital ratios have a negative impact. Additionally, the study reveals the influence of regional factors and auditor rank on financial performance, emphasizing the complex interplay between financial metrics and the valuation of intangible assets. These insights contribute to understanding earnings management behaviours and provide practical implications for financial management in R&D-intensive entities.